Cuantificación electroquímica simultanea de pb(ii), cd(ii) y zn(ii) en sedimentos marinos superficiales utilizando microelectrodo de carbono. - Sánchez Sarango, Mireya Belén (2022)
Heavy metals are considered dangerous elements due to the pollution and damage they generate in the environment when they exceed the permissible limits, in addition to their characteristic of not being biodegradable. Marine sediments are described as reservoirs of metals and possible sources of pollution, since they act as elemental integrators and concentrators, allowing transport and adherence with biological membranes of different species, which can cause various damages. In the present investigation, the development of a disposable, sensitive, simple and low-cost voltammetry sensor from carbon fiber is presented, which allows the simultaneous detection of Pb (II), Cd (II), and Zn (II) in marine sediments, making possible the analysis of these elements of interest and generating mitigation alternatives in the future. For this, parameters related to the proposed technique were optimized, such as electrolytic solution, carbon fiber treatment, optimization of the technique for quantification, time and pre-concentration potential. The technique used was differential pulse voltammetry, with which linear relationships were obtained for the quantification of metals in ranges of 12 to 50 ug/ml for both Pb (II), Cd (II) and Zn (II); additionally, the detection limits obtained were 2,60 ug/l; 0,76 ug/l y 5,78 ug/l, respectively. Finally, the sensor was applied in the quantification of Pb, Cd and Zn in marine sediments from Puerto Jeli in the province of El Oro; since it is representative of the contamination present in the coastal profile of the province due to the mishandling of fuels (such as diesel, gasoline and oils), gas extraction, illegal mining, as well as painting of artisanal fishing boats, which are used indiscriminately. The results achieved outline the sensor as a promising and reliable tool for metal analysis that could be extended to other research areas.